Implementation of Delivery Insurance Policy (Jampersal) At the Health Department of North Minahasa District - Maya Nursin; Itje Pangkey; Fitri Herawaty Mamonto (International Journal on Integrated Education, 2022)
This Maternity Guarantee is a program that aims to help the underprivileged in terms of childbirth costs to reduce maternal and infant mortality, and the targets of this maternity insurance are pregnant women, mothers in labor, postpartum and neonatal mothers. However, after field observations were made by researchers, it was found that the socialization of the program had not been maximized. So that the objectives of this research are: a. To describe and analyze the implementation of the Maternity Guarantee Program policy in North Minahasa Regency. b. To describe and analyze the determinants of the implementation of the Maternity Insurance Policy in North Minahasa Regency, North Sulawesi Province. The method used in this study is a qualitative research method, where the focus of the first research is a Maternity Guarantee participants target, b. The procedure for the implementation of maternity financing. The second research focus a. Effective socialization, b. Competent resources. Sources of data used in this study using semi-structured interview techniques and documentation. Interviews were conducted with the Health Office and Puskesmas and the community in Kab. North Minahasa, North Sulawesi Province. The results of this study are 1. Effective Socialization: The Maternity Insurance Program has been socialized in health service facilities in North Minahasa district, but it has not been maximized because there are still people who do not know about this Maternity Insurance program. 2. Competent Staff Resources: